Factors Associated with Nursing Career Path at Prof. Hospital. Dr. Tabrani Pekanbaru in 2024.: Faktor Yang Berhubungan Dengan Jenjang Karir Perawat Di Rumah Sakit Prof. Dr. Tabrani Pekanbaru Tahun 2024. - Tasya, Nur; Raviola, Raviola; Wahyudi, Arief; Arnawilis, Arnawilis; Natassa, Jihan (Badnur Medisa Group, 2024)
A career path is a formal, planned and organized effort to achieve a balance between an individual's career needs and the demands of work in an organization. At Tabrani Hospital, there are still nurses with a long working period who still do not have a good career path or have improved. The variables in this study are dependent variables, namely the career path of nurses and independent variables, namely education, training, employment period, and promotion. This research was conducted to see if there is a relationship between education, training, work period, and promotion with the career path of nurses at Prof. Dr. Tabrani Hospital Pekanbaru in 2024. The location of the research was carried out at Tabrani Hospital Pekanbaru in March-July 2024,This study is a quantitative, cross sectional research design. This study was conducted at Prof. Dr. Tabrani Hospital Pekanbaru, the population in this study amounted to 66 nurses, with a sample of 57 nurses. Data analysis was carried out univariate and bivariate with chi-square test (α=0.05). The results of bivariate analysis showed that there was no significant relationship between education (p = 0.705 <α=0.05), no relationship between working period (p = 0.346 <α=0.05), no relationship between training (p = 0.551 <α=0.05), and there was a relationship between promotion (p = 0.046 <α=0.05) and nurse's career path. Based on the results of the research, it was concluded that there was no relationship between education, working period, training, and there was a relationship between promotion and nurse career path.So the suggestion for hospitals to pay more attention to the main thing so that it can be beneficial for nurses and the hospital itself. Where both parties feel benefited in achieving the expected work results.